2001
DOI: 10.1186/bcr285
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of soy intake and mammographic characteristics in Hawaii

Abstract: BMI = body mass index; CI = confidence interval; FFQ = food frequency questionnaire; icc = intraclass correlation coefficients; SQ = soy questionnaire; κ w = weighted Kappa statistics. AbstractThis cross-sectional investigation in Hawaii explored the relation between soy foods and mammographic characteristics using two food frequency questionnaires and a computer-assisted density assessment method. Japanese and Chinese women reported significantly greater soy food intake than Caucasian women. Whereas soy inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 28 publications
3
43
1
Order By: Relevance
“…Our results were consistent with those from previous studies (22,23). Soy intake was positively associated with percent density among Caucasian and Native Hawaiian women but not in the Chinese and Japanese women living in Hawaii (22).…”
supporting
confidence: 83%
“…Our results were consistent with those from previous studies (22,23). Soy intake was positively associated with percent density among Caucasian and Native Hawaiian women but not in the Chinese and Japanese women living in Hawaii (22).…”
supporting
confidence: 83%
“…In contrast to the findings of randomized trials, most (12,(31)(32)(33) but not all (34) cross-sectional studies show that women with high habitual consumption of soy have lower mammographic density. This might suggest that the duration of the intervention in the trials was too short.…”
Section: Discussioncontrasting
confidence: 39%
“…These data suggest that short-term dietary soy supplementation can induce proliferation in breast tissue of premenopausal women with breast disease. In contrast, soy consumption has been associated with a reduction of mammographic density (Atkinson & Bingham 2002, Jakes et al 2002, whilst Maskarinec & Meng (2001) reported a positive correlation between self-reported soy food intakes and percentage breast density in women living in Hawaii. Increased mammographic density has been associated with a four-to sixfold increased risk of breast cancer (Atkinson et al 1999).…”
Section: Human Studiesmentioning
confidence: 99%